Krieg, Robert A., Treasure in the Field: Salvation in the Bible and in Our Lives - Jakub Urbaniak (Acta Theologica)
In this concise book, Robert Krieg recasts the soteriological insights of the Bible in psychological-existential terms, i.e., by reflecting on salvation as God’s gift of one’s personal wholeness. Jesus’ parable about the person who finds “treasure hidden in a field” (Matt 13:44) constitutes the backbone of Krieg’s interpretation: God creates us as “treasures buried in the field” and thus discovering our true selves is the only way toward the “accomplishment” of God’s salus in our lives. Salvation thus comprehended involves both being released by God from whatever prevents or resists our maturation into the whole person whom God intends, and the completion of our personal existence through union with God in eternal life.